2004
DOI: 10.1128/aem.70.5.2748-2755.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adaptation to Ethanol on Cytoplasmic and Membrane Protein Profiles of Oenococcus oeni

Abstract: The practical application of commercial malolactic starter cultures of Oenococcus oeni surviving direct inoculation in wine requires insight into mechanisms of ethanol toxicity and of acquired ethanol tolerance in this organism. Therefore, the site-specific location of proteins involved in ethanol adaptation, including cytoplasmic, membrane-associated, and integral membrane proteins, was investigated. Ethanol triggers alterations in protein patterns of O. oeni cells stressed with 12% ethanol for 1 h and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 50 publications
2
80
0
Order By: Relevance
“…In relation to this, with the aim of determining the protein profile of the B. longum envelope, and as a first approach to undertaking deeper functional studies, we analysed different subcellular fractions. The application of gel-based and gel-free technologies, combined with high-throughput techniques, allowed us to identify 218 proteins; about 70 % of them were predicted to be, or were previously described as being, in the cell envelope of Gram-positive bacteria (Antikainen et al, 2007;Candela et al, 2007;Eymann et al, 2004;Granato et al, 2004;Jang & Hanash 2003;Kelly et al, 2005b;Nandakumar et al, 2005;Rivera-Amill et al, 2001;Rodríguez-Ortega et al, 2006;Schaumburg et al, 2004;Severin et al, 2007;Silveira et al, 2004;Tjalsma et al, 2008;Wolff et al, 2007). Furthermore, 48 of them are predicted to be integral membrane proteins (contain hypothetical transmembrane segments) and 30 of them have different extracytoplasmic sorting signals.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, with the aim of determining the protein profile of the B. longum envelope, and as a first approach to undertaking deeper functional studies, we analysed different subcellular fractions. The application of gel-based and gel-free technologies, combined with high-throughput techniques, allowed us to identify 218 proteins; about 70 % of them were predicted to be, or were previously described as being, in the cell envelope of Gram-positive bacteria (Antikainen et al, 2007;Candela et al, 2007;Eymann et al, 2004;Granato et al, 2004;Jang & Hanash 2003;Kelly et al, 2005b;Nandakumar et al, 2005;Rivera-Amill et al, 2001;Rodríguez-Ortega et al, 2006;Schaumburg et al, 2004;Severin et al, 2007;Silveira et al, 2004;Tjalsma et al, 2008;Wolff et al, 2007). Furthermore, 48 of them are predicted to be integral membrane proteins (contain hypothetical transmembrane segments) and 30 of them have different extracytoplasmic sorting signals.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial exposure to stress factors such as low pH, ethanol or low temperatures, induces membrane changes that are well documented in the literature. These membrane changes include the decrease in the membrane fluidity as a result of alterations in the fatty acid composition (Bastianini et al 2000;Chu-Ky et al 2005), or the induction of small heat shock proteins LO18 (Guzzo et al 1997), and accordingly modification of both cytoplasmic and membrane protein profiles (Silveira et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study with the gram-positive organism Bacillus subtilis, it was demonstrated that treatment with subinhibitory concentrations of ethanol (not affecting vegetative growth) inhibited the initiation of spore development through a selective blockage of key developmental genes under the control of the master transcription factor Spo0AϳP (14). These toxic effects have been described for a wide variety of microbial species, and for use of different concentrations of ethanol, ranging from 2.5% to 70% (1,2,8,10,19,25,36). Surprisingly, very little is known about the physiological effects of VLEC.…”
mentioning
confidence: 99%
“…The bactericidal activity of ethanol is due to several factors: disruption of membrane structure or function (1,12,15,36); interference with cell division, affecting steady-state growth (12); variations in fatty acid composition and protein synthesis (8); inhibition of nutrient transport via membrane-bound ATPases (4); alteration of membrane ⌬pH (4, 40) and membrane potential (⌬) (40); and a decrease in intracellular pH (4,18,40). In a recent study with the gram-positive organism Bacillus subtilis, it was demonstrated that treatment with subinhibitory concentrations of ethanol (not affecting vegetative growth) inhibited the initiation of spore development through a selective blockage of key developmental genes under the control of the master transcription factor Spo0AϳP (14).…”
mentioning
confidence: 99%